Dementia in later life : research and action, report of a WHO Scientific Group on Senile Dementia, meeting held in Paris from 30 August to 5 September 1983 - WHO Scientific Group on Senile Dementia; World Health Organization (Geneva : World Health Organization, 1986)
Reports the work of a scientific group convened to review biomedical and health service research on demential disorders in old people. Research strategies for improving knowledge of etiology, treatment, and prevention are stressed throughout. Specific problems include the need to establish core diagnostic criteria, the effective use of epidemiological investigations to increase scientific knowledge, the definition of appropriate support systems for coping with dementia, and strategies for promoting interdisciplinary and intercountry collaborative research. The most extensive section covers the many lines of investigation focused on determining the causes of Alzheimers disease, including present and recommended research in the fields of neuropathology, neurochemistry, neurophysiology, cell biology and molecular biology. Close to 200 references are included
1. Introduction -- 2. Diagnostic considerations -- 3. The burden of the dementias -- 4. The epidemiology of senile dementia -- 5. Alzheimer's disease : The search for causes -- 6. Prevention and treatment -- 7. Coping with dementia -- 8. International collaborative research on dementias -- 9. Conclusions and overall strategic issues -- Acknowledgements -- References
Keywords: Dementia; Health of Special Groups